2015
DOI: 10.1002/acr.22510
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Biologic Agents With and Without Concomitant Methotrexate and at Reduced Doses in Older Rheumatoid Arthritis Patients

Abstract: Background This study examines whether concomitant methotrexate (MTX) use is associated with better biologic persistence and whether self-administered anti-TNF therapies are used at reduced doses in real-world clinical care settings, not just clinical trials. Methods We conducted a retrospective cohort study among RA patients using Medicare claims data from 2006 to 2012. Subjects were new initiators of etanercept, infliximab, adalimumab, abatacept and tocilizumab with at least 12 months of continuous medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 33 publications
7
28
0
2
Order By: Relevance
“…On the other hand, there are studies which similar to the current study did not find previous biological therapy usage as a negative predictor of persistence (11,16,20,21,23). Although concomitant MTX usage has been shown to be associated with a better persistence of biologicals in rheumatological settings, there is no conclusive evidence in psoriasis about additional MTX as a positive predictor (24,25). In a systematic review, Bezooijen et al selected eight studies, which generally showed that combination therapy of biologicals and MTX had higher efficacy than biological monotherapy, which could also indicate a positive effect of MTX on the drug survival; however, persistence was not investigated in this study (26).…”
Section: Discussionsupporting
confidence: 49%
“…On the other hand, there are studies which similar to the current study did not find previous biological therapy usage as a negative predictor of persistence (11,16,20,21,23). Although concomitant MTX usage has been shown to be associated with a better persistence of biologicals in rheumatological settings, there is no conclusive evidence in psoriasis about additional MTX as a positive predictor (24,25). In a systematic review, Bezooijen et al selected eight studies, which generally showed that combination therapy of biologicals and MTX had higher efficacy than biological monotherapy, which could also indicate a positive effect of MTX on the drug survival; however, persistence was not investigated in this study (26).…”
Section: Discussionsupporting
confidence: 49%
“…This pivotal drug works in synergy with biologic agents, increasing their efficacy, and older patients receiving combination therapy (methotrexate and anti-TNF) have higher persistence than those on biologics monotherapy, with the strongest associations being observed for infliximab and adalimumab [41].…”
Section: Treatment Of Elderly Ra In the XXI Centurymentioning
confidence: 99%
“…Other confounding factors that could be monitored to prove biological safety and efficacy of biologics in this particular population are largely 13 missing (such as steroid decrease). Drug adherence is significantly higher in older patients concomitantly taking methotrexate [41,46].…”
Section: 12tolerability and Safetymentioning
confidence: 99%
“…В ретроспективное исследование J. Zhang и соавт. [74] было включено 26 510 пациентов пожилого возраста с РА, наблюдавшихся в рамках программы Medicare (феде-ральная программа медицинского страхования для населе-ния старше 65 лет). Авторы исследовали связь между при-емом МТ и длительностью приема ГИБП, включая ЭТЦ, ИНФ, АДА, абатацепт (АБЦ) и ТЦЗ.…”
Section: эффек тивностьunclassified